Lairds and gentlemen: a study of the landed families of the eastern Anglo-Scottish Borders c.1540-1603 - Meikle, Maureen Manuel (University of Edinburgh, 1988)
The main purpose of this thesis is to present a thematic and comprehensive study of the lairds and gentlemen of the Eastern Anglo-Scottish Borders from 1540 ýoIG03 The basic themes of this study embrace the social structures of the landed communities on both sides of the international frontier, their politics, wealth, education and culture, religion, disorders and cross-border relations. Comparison and contrast across the Border has been undertaken for all these themes. This approach has illuminated how local Scottish and English societies functioned in the sixteenth and early seventeenth centuries. Strong kinship was prominent on both sides of the frontier and permeated all aspects of society, as well as affecting the interference of crown and court politics in these localities. Intermeddling from both centres of government disturbed the local communitiýs. but the lairds and gentlemen remained in overall control of their local spheres of influence. They were the backbone of local government in the Eastern Borders for they dominated domestic offices, but they were also able to gain offices in the administration of the Borders. Their wealth, as far as this can be ascertained, was broadly similar and their standard of education and culture was at a higher level than has previously been acknowledged. The effects of the English and Scottish Reformations in the Eastern Borders were typified by a slow enforcement of Protestantism, but overt recusancy was much stronger in the Eastern English Borders where over 50% of the gentry were still Catholic in 1603. The disorders of this region have been exaggerated for they were, in reality, not untypical of landed society elsewhere in England and Scotland in the sixteenth century. Finally, the cross-border relations of the Eastern Borders indicate general familiarity and friendships between the landed families that were far-removed from the typical image of the Borderer as a violent cattle thief. The lairds and gentlemen were known to socialize amongst themselves with scant regard of the international frontier, as the river Tweed was not a physical barrier to communication. There was also a significant amount of trading across the Border in flesh, grain and horses. This activity was often regarded as illegal in both Scotland and England, but it was beneficial to the lairds and gentlemen and therefore thrived under their protection
Keywords: History